2019
DOI: 10.1108/jfbm-11-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Family firms’ innovation drivers and performance: a dynamic capabilities approach

Abstract: Purpose Entrepreneurial innovation has been the most important source for improvement in firm performance. Innovation in family firms has become the focal issue in firm strategy. In today’s high-velocity environment, the dynamic organizational adaptation is essential for sustainable competitive advantage. The purpose of this paper is to investigate the nature of changes in external environment and the relationship between changes in the economic environment and family firms’ innovation in response to the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 61 publications
1
34
0
6
Order By: Relevance
“…Consequently, this article aims to empirically test the concept of the familiness learning mechanism in an effort to address the paucity of empirical studies and so analyze dynamic capabilities in family businesses (Park et al, 2019). To operationalize the concept in the context of family firms, we use the factor analysis technique and a second-generation technique, partial least squares structural equation modeling (PLS-SEM).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this article aims to empirically test the concept of the familiness learning mechanism in an effort to address the paucity of empirical studies and so analyze dynamic capabilities in family businesses (Park et al, 2019). To operationalize the concept in the context of family firms, we use the factor analysis technique and a second-generation technique, partial least squares structural equation modeling (PLS-SEM).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Oliva et al (2018) measured dynamic capabilities by integration of individuals' expertise in the organization; culture, orientation and leadership; and corporate strategies. The other dimensions are markets, technologies and regulations (Park et al, 2018) sensing, seizing, transforming (Tallott & Hilliard, 2016) the ability to identify and explore emerging opportunities and new sources of competitive advantages (Bamel & Bamel, 2018;Schilke et al, 2018) sensing, learning, integrating, and coordinating capability (Hernández-Linares et al, 2021) strong coordination, and competitive response to the rivals (Rehman & Saeed, 2018).…”
Section: Dynamic Capabilities and Digital Ecosystemmentioning
confidence: 99%
“…According to the research by Gnizy et al (2014), dynamic capabilities affect the success factors of SMEs, one of which is to go digital. Further research by Park et al (2018) showed that dynamic capabilities as measured by market conditions, technology and regulation that affect company performance in driving digital business (Oliva et al, 2018;Rialti et al, 2019;Tallott & Hilliard, 2016). Thus, the hypothesis is formulated as follows: H3: The higher the dynamic capabilities of SMEs, the higher the digital ecosystem.…”
Section: Dynamic Capabilities and Digital Ecosystemmentioning
confidence: 99%
“…While Oliva et al (2018) measured dynamic capability by the integration of individuals' expertise in the organization, culture, orientation and leadership, and corporate strategies. Other dimensions are markets, technologies, and regulations (Park et al, 2018). Whereas sensing, seizing, transforming were measured by Tallott & Hilliard (2016).…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%